"We are not in this to save the polar bears!" – the link between community renewable energy development and ecological citizenship. Issue 3 (2nd July 2016) - Islar, Mine; Busch, Henner
Abstract : The transition from a fossil fuel-based energy system to a renewable one has emerged as a priority for many governments. This, in turn, has facilitated a rapid increase in renewable energy investments. However, this development raises important questions about the sustainability of energy governance when it comes to access and control of energy, public participation and transparency. In this article, decentralized renewable energy production is presented as one of the pathways towards more participation in sustainable energy development. Community renewable energy projects help to enable communities to act as citizens, rather than consumers. In this article, we aim to understand the interactions between community renewable energy transition and collective practices of citizenship. We investigate collective practices in energy development within the ecological citizenship framework by addressing the extent to which each community's energy project displays the characteristics of ecological citizenship, in terms of how their collectivity is organized, articulated and shaped the future goals and vision. Based on the empirical data collected in Feldheim (Germany) and Samsø (Denmark), we find out that when collectivity is embedded in community renewable energy development, it resonates with the particularities of communitarian ecological citizenship that has a local focus rather than a political focus, and primarily prioritizes the cohesiveness and interests of the community (i.e. economic development) rather than the global commitment to sustainability discourses (i.e. climate change). This article also raises questions about the importance of intentionality in bringing about ecological outcomes of renewable energy transitions.